Direct Nucleophilic Substitution of Free Allylic Alcohols in Water Catalyzed by FeCl3⋅6 H2O: Which is the Real Catalyst?. Issue 6 (12th February 2013) - Trillo, Paz; Baeza, Alejandro; Nájera, Carmen
Abstract The allylic substitution reaction, and particularly the direct allylic amination reaction, of free allylic alcohols in water catalyzed by FeCl3⋅6 H2O is described. This novel environmentally‐friendly methodology allows the use of a wide variety of nitrogenated nucleophiles such as sulfonamides, carbamates, benzamides, anilines, benzotriazoles, and azides, generally giving good yields of the corresponding substitution products. The synthetic applicability of the process is also demonstrated because the reaction can be performed on gram‐scale. Additionally, carbon nucleophiles such as silylated nucleophiles, aromatic compounds, and malonates also proved to be suitable for this transformation. Finally, the nature of the catalytic species present in aqueous media is unveiled, pointing towards the formation of hexaaquo iron(III) complexes.